Disaster Abrasion Mitigation Education Through Introducing the Role of Coastal Vegetation to Students of SMPN 1 Pantai Cermin - Azzahro, Nur Hafizah; Susilawati; Harahap, Jihan Fadhilah; Lubis, Mafaza Auliya; Nurhaliza, Indah (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
The phenomenon of global sea level rise is accelerating the rate of erosion that threatens the stability of coastal areas in various countries. As an archipelagic country with extensive coastlines, Indonesia faces serious risks from prolonged coastal erosion along its coastline, which spans hundreds of thousands of kilometers. Indonesia's coastal areas are vulnerable to coastal erosion, which impacts both the environment and settlements. Pantai Cermin District, Serdang Bedagai Regency, is one of the areas experiencing significant erosion. One sustainable non-structural mitigation effort is through environmental-based education, particularly the introduction of the role of coastal vegetation. This study aims to determine the effect of disaster mitigation education on abrasion through the introduction of the role of vegetation on the improvement of knowledge and awareness of students at SMP Negeri 1 Pantai Cermin. The study uses a quantitative approach with a pretest–posttest design involving 60 students. Instruments. The research instruments consisted of questionnaires and knowledge tests. Based on the collected data, there was a significant increase in the understanding scores from an average of 10.85 before the intervention to 14.58 after the material was delivered. These findings indicate that vegetation-based coastal abrasion mitigation education is effective in increasing students' knowledge and awareness of coastal erosion.